1992
DOI: 10.1089/dna.1992.11.539
|View full text |Cite
|
Sign up to set email alerts
|

The Retinoblastoma Protein Region Required for Interaction with the E2F Transcription Factor Includes the T/E1A Binding and Carboxy-Terminal Sequences

Abstract: Recent experiments in understanding the mechanism of the retinoblastoma protein (RB) function have revealed the existence of several cellular proteins that are complexed with RB. One of these cellular proteins is the E2F transcription factor, which was originally identified due to its inducibility by E1A during an adenovirus infection. The E2F recognition sequence is found in the promoters of several cellular genes involved in growth control, including several oncogenes. In this report, we provide evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…Competitor wt consists of identical E2F sequences from the E2 promoter. Competitor A consists of a C-to-A mutation in each E2F site, and this mutant site exhibits reduced E2F binding (35). A typical E2F EMSA utilized 3 to 5 g of muscle cell extract and 0.1 ng of 32 P-labelled E2F probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Competitor wt consists of identical E2F sequences from the E2 promoter. Competitor A consists of a C-to-A mutation in each E2F site, and this mutant site exhibits reduced E2F binding (35). A typical E2F EMSA utilized 3 to 5 g of muscle cell extract and 0.1 ng of 32 P-labelled E2F probe.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of RB, this pocket region is the site of tumorigenic inactivating mutations and is critical for the growth suppression function of RB. We and others have demonstrated that E2F binds to this region, providing a genetic correlation between E2F binding and growth suppression (1,3,8,9,32,35,56,57; for additional reviews, see references 28, 44, and 53). Different E2F complexes with RB or p107 are found during the G 1 and S phases of the cell cycle.…”
mentioning
confidence: 90%
“…Seven of these sites are contained within a 50 amino acid stretch within the C-terminal domain of the protein. This domain is sucient for c-Abl binding (Welch and Wang, 1993) and is required for association with many non-LXCXE containing pRb-associated proteins like E2F-1 (Huang et al, 1992;Qin et al, 1992). Two sites are located in the spacer region between the A and B domains.…”
Section: Rb Glutamic Acid Substitution Mutantsmentioning
confidence: 99%
“…A truncated RB1 composed of the A/B pocket and the C-terminus, which now includes the E2F-binding region (Huang et al, 1992), is able to act as a functional domain in the absence of the N-terminal region. Overexpression of the full length pRb in Saos-2 cells arrested these cells in G 1 and produced a large, at cell morphology.…”
Section: Introductionmentioning
confidence: 99%